Assessment of Thyroid Disorder during Pregnancy in Tertiary Level Hospital, Nepal - Sapkota, Kalyan; Adhikari, B. R.; Dhakal, B. (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Thyroid dysfunctions are most prevalent in women during their most fertile years (15 - 35) and thyroid dysfunction during pregnancy is associated with higher risk of pregnancy and neonatal complications. Routine screening of thyroid dysfunction during pregnancy can help to identify and treat the disorder early and prevent its complication.Methods: A hospital based observational study on 400 pregnant women was conducted in tertiary level hospital in Nepal. Participants with abnormal thyroid functions were regularly followed up till the pregnancy outcome.Results: Among 400 cases, 45.3% of the respondents were of age group 21-25 years with mean age 23.84 ±3.5 years. This study had 14.7 % (n 59) women with abnormal thyroid functions. Of these 12.7 % were hypothyroid and 2 % were hyperthyroid. Among 51 cases of hypothyroid 10.5 % were subclinical hypothyroid and 2.2 % were overt hypothyroid. Majority of the pregnant women with thyroid dysfunction had one or more adverse events during pregnancy course.Conclusion: Thyroid dysfunction is common during pregnancy. High prevalence of thyroid dysfunction necessitates the standardized screening protocol to pregnant women based on risk categories and early initiation of treatment if significant abnormality is identified and regular follow up for every pregnant woman with abnormal thyroid function.